1989
DOI: 10.1128/jb.171.10.5720-5728.1989
|View full text |Cite
|
Sign up to set email alerts
|

Beta-lactam biosynthesis in a gram-negative eubacterium: purification and characterization of isopenicillin N synthase from Flavobacterium sp. strain SC 12.154

Abstract: The occurrence, localization, and extraction of isopenicillin N-synthase (IPNS) were investigated in the gram-negative low-level 13-lactam producer Flavobacterium sp. strain SC 12.154, which forms deacetoxycephalosporin and excretes the cephabacin 7-formamidocephalosporin. IPNS was detected with anti-IPNS antibodies raised against the Cephalosporium acremonium enzyme. The flavobacterium enzyme, whose molecular mass (38 kilodaltons) and cofactor requirements resemble those of the fungal and Streptomyces enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The regulation of these CH␤Ls, if any, would be of interest as described for the A. hydrophila CH␤L (1). It may be hypothesized that CH␤Ls in C. meningosepticum may counteract the effect of antibiotics produced by this Chryseobacterium species (33,37). Additionally, the presence of two CH␤L genes in C. meningosepticum may be used as a tool for a PCR-based identification of this species.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of these CH␤Ls, if any, would be of interest as described for the A. hydrophila CH␤L (1). It may be hypothesized that CH␤Ls in C. meningosepticum may counteract the effect of antibiotics produced by this Chryseobacterium species (33,37). Additionally, the presence of two CH␤L genes in C. meningosepticum may be used as a tool for a PCR-based identification of this species.…”
Section: Discussionmentioning
confidence: 99%
“…IPNS was purified to homogeneity from A. chrysogenum (27,142,251) and has subsequently been obtained from P. chrysogenum (267), A. nidulans (339), several actinomycetes such as S. clavuligerus (153), and the gram-negative bacterium Flavobacterium sp. (250). It was shown that two interconvertable forms of the enzyme exist, an oxidized state with a disulfide linkage and a reduced state (27).…”
Section: Structural Genes and Deduced Proteinsmentioning
confidence: 99%
“…These species, along with Streptomyces clavuligerus ATCC 27064 (DSM 738), S. lactamdurans ATCC 27382 (NRRL 3802), Streptomyces jumonjinensis ATCC 29864, and Flavobacterium sp. strain SC 12.154 (Squibb) (30) were maintained on 2% Bacto agar (Difco) containing 1% glycerol (Fisher), 0.5% * Corresponding author. yeast extract (Difco), and 0.5% malt extract (Difco).…”
mentioning
confidence: 99%